Assistance in Monitoring Risk Management of Electronic-Based Government Systems (SPBE) at the Bandung City Communication and Informatics Office - Endah Mustika Ramdani; Elsa Wafa Salsabila (TGO Journal of Community Development, 2024)
The implementation of the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik/SPBE) requires effective risk management to ensure the continuity, security, and quality of digital public services. However, the Bandung City Government still faces several challenges, including the inconsistent implementation of SPBE risk management across regional government agencies, the absence of an integrated digital platform for risk monitoring, and inconsistencies in risk identification. This community service activity aimed to strengthen the implementation of SPBE risk monitoring at the Bandung City Communication and Informatics Office (Diskominfo) through active participation in planning, monitoring, and reporting processes. The activity employed a participatory approach based on the Indonesian National Work Competency Standards (SKKNI) for Development Planning, encompassing four stages: identification and observation, data collection, development planning formulation, and preparation of progress reports. The activities included compiling SPBE risk management documents, monitoring risk implementation, assisting in the preparation and verification of the Regional Work and Budget Plan (RKA), and contributing to the preparation of performance accountability reports, including the Government Agency Performance Report (LKIP), Regional Government Accountability Report (LKPJ), and Internal SPBE Audit Report. The results indicate that these activities contributed to improving the quality of SPBE risk management documentation, strengthening coordination among organizational units, and supporting better planning and accountability processes. Furthermore, the activity generated recommendations to enhance SPBE governance through standardized risk management practices, continuous monitoring, and the development of an integrated digital platform to support sustainable electronic government governance.